Numerical modelling of the Sydney Harbour Estuary, New South Wales: Lateral circulation and asymmetric vertical mixing. (5th February 2019) - Xiao, Ziyu; Wang, Xiao Hua; Roughan, Moninya; Harrison, Daniel
Abstract: A fully calibrated three-dimensional hydrodynamic model of the Sydney Harbour Estuary was used to determine the dominant forcing of regulating estuarine circulation in a sinuous channel under conditions of low river discharge during dry weather. The system, characterized by stratified flood and mixed ebb during spring tides, and stratified flood and ebb during neap tides, was analysed using model results of current profiles, density field, eddy viscosity and gradient Richardson number at a mooring station and cross-channel transect. The magnitude and direction of lateral circulation was modulated in the flood-ebb and spring-neap cycles due to changes in the interactions between the tides and the complex geometry. During spring tides, a differential-advection-induced lateral baroclinic pressure gradient tends to drive the lateral circulation and stratifies the water column. When the along-estuary circulation is strong enough to break the stratification induced by the lateral baroclinic pressure gradient, centrifugal force works in concert with nonlinear advection establishing a classical two-layer helical flow across the channel. Channel bends also induce vertical mixing as a result of the overturning of the density fields. The lateral circulation redistributes the differential-advection-induced lateral shear of the along-estuary momentum and is transferred to either reinforce or cancel the along-estuary circulation. The lateral bathymetry variability in a channel is therefore the key factor causing the intratidal asymmetries in the along-estuary circulations. Stratification suppresses lateral circulation during neap tides, and generates a three-layer lateral circulation structure in the water column during stratified ebb. Highlights: The interaction between stratification, tides and the complex geometry produces asymmetries in the lateral circulation. Lateral circulation induces the asymmetries in the vertical mixing. Along-estuary momentum is transformed by the lateral circulation leading to asymmetries in the along-estuary circulation. Channel bends transfer along-estuary circulation into lateral circulation and vertical mixing.